2015
DOI: 10.1016/j.jinorgbio.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-based complexes with N-(acyl)-N′,N′-(disubstituted)thiourea ligands: Synthesis, characterization, BSA- and DNA-binding studies of new cytotoxic agents against lung and prostate tumour cells

Abstract: Four ruthenium(II)-based complexes with N-(acyl)-N',N'-(disubstituted)thiourea derivatives (Th) were obtained. The compounds, with the general formula trans-[Ru(PPh3)2(Th)(bipy)]PF6, interact with bovine serum albumin (BSA) and DNA. BSA-binding constants, which were in the range of 3.3-6.5×10(4) M(-1), and the thermodynamic parameters (ΔG, ΔH and ΔS), suggest spontaneous interactions with this protein by electrostatic forces due to the positive charge of the complexes. Also, binding constant by spectrophotomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 64 publications
4
30
0
2
Order By: Relevance
“…To the best our knowledge, there is no paper published related to the octanoyl thiourea. However, Correa et al (2015) reported the BSA-and DNAbinding studies of thiourea complexes against lung and prostate tumor cells. The antimicrobial activities of thioureas were reported in which few derivatives were found to be good against E. coli (Zhong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To the best our knowledge, there is no paper published related to the octanoyl thiourea. However, Correa et al (2015) reported the BSA-and DNAbinding studies of thiourea complexes against lung and prostate tumor cells. The antimicrobial activities of thioureas were reported in which few derivatives were found to be good against E. coli (Zhong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The distances for the Ru-Cl, Ru-P and Ru-N bonds lengths and bond angles found for the compound is within the normal range for similar ruthenium(II) complexes. 12,25,27 In Figure 2A the six rings of the dpqQX ligand labeled (a-f) are depicted. Rings a and b are connected with the ruthenium(II), while rings c-f (tetraaza center) are in the outer-coordination sphere responsible for intermolecular interactions.…”
Section: P{mentioning
confidence: 99%
“…Complexes 1 and 2 are also active, presenting IC 50 values comparable with other ruthenium(II)/phosphine complexes. 11,12,27 The isomer cis-[RuCl 2 (dppb)(dpqQX)] (2) is more active than the trans-[RuCl 2 (dppb)(dpqQX)] (1) one. Probably, due to the lability of the chlorine ligand trans to a phosphorus atom, forming the cationic species [RuCl(L)(dppb)(dpqQX)] + (where L = solvent), such as occur in analogous complexes.…”
Section: Antitumoral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…ese benzoylthiourea derivatives (BTU) proved to have excellent properties to bind to various metal ions due to the very strong donor groups (carbonyl and thioamide) that yield various transition metal complexes. e BTU ligands can give neutral homoleptic or heteroleptic complexes either with S-and Ocoordination, when the ligand is coordinated in monoanionic bidentate form by deprotonation or with only S-coordination if the ligand is bound in neutral form to the metal center [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%